Catholicism, Psychedelics, and Mysticism: Correlations and Displacements - Slatter, Mark (Religions, 2024)
This article charts some of the conversations around psychedelics, mysticism, Catholicism, and the Catholic mystics. The first part, “Background and Orientation”, gives context for the current “psychedelic renaissance” and brings the focus to psychedelics and Catholicism. The literature’s frequent comparisons of psychedelic mystical trips with Catholic mysticism raises questions about the legitimacy of religious ways of knowing, the status of the discipline of theology in Western academic cultures, and how Catholicism is often depicted in the psychedelic literature. The first part closes with a survey of the challenges of defining mysticism and some of the patterns perennial to the Catholic mystical experience. In the second part, “Through the Eye of the Methodology Needle”, I look at the problem of methodological displacement, that is, how a researcher comes to conclusions with material that is formally outside of their discipline’s boundaries. This is a challenge for scholars of every stripe when they countenance subject matter that is beyond their expertise—and the lure to still read that material through their known methodology and worldview—but the problem of displacement is conspicuously compounded when the sciences countenance theological and religious themes. I provide concrete examples of displacement with psychedelic and Catholic mysticism, how it can be corrected, and how this would benefit dialogue. In the Conclusions, I outline persistent concerns and theological objections about some of the claims of psychedelic mysticism but hold onto the hope for further dialogue. My sustained attention is to the comparisons that are frequently made between the psychedelic and Catholic mystical experiences and whether these correlations are critically warranted.